(untitled) (Nigerian Journal of Cooperative Economics and Management, 2021)
This study examined the effect of cooperative membership on recovery of flood victims who have had their income, output and productivity levels altered and subsequently reduced. This study was propelled by the inconclusiveness of previous studies on the mechanisms for mitigating the impact of flooding and the need to justify the emphasis of cooperative membership as a better alternative for the recovery of flood victims. The objectives of the study were to analyze the effect of flooding on the economic activities in Anambra State and to determine the contributions of cooperatives to the recovery of flood victims. The area of study was Anambra state. Ogbaru LGA was purposively selected as it was observed to have had repeated event of flooding since 2012. Eight out of sixty five functional cooperatives in the LGA were selected as the sample. Questionnaires were randomly distributed to members of the cooperatives. The study adopted descriptive survey method and analysis was done using simple percentage and frequency distribution model to measure the demographic profile of respondents, specific objectives were analyzed using mean while the research hypothesis were tested using simple regression analysis. The study revealed that flooding has affected the income levels of victims as well as their savings behaviors and consumption pattern. Cooperatives contributed to recovery of flood victims by providing micro-credits, education and extension services, seminars and local level capacity building. This study therefor recommended among others that flood insurance knowledge and forecasting be made available, access to micro-credits by victims, increased capitalization of cooperatives, all necessary assistance to victims should pass through cooperatives, checks and balances and increased awareness of the relevance of cooperative membership to recovery of flood victims.